Abstinence following intermittent methylphenidate exposure dose‐dependently modifies brain glucose metabolism in the rat brain. Issue 9 (30th June 2022) - Arnavut, Eliz; Hamilton, John; Yao, Rutao; Sajjad, Munawwar; Hadjiargyrou, Michael; Komatsu, David; Thanos, Panayotis K.
Abstract: Methylphenidate (MP) is a psychostimulant chronically prescribed for the treatment of attention deficit hyperactivity disorder (ADHD). Additionally, MP users may take breaks from using the medication during "drug holidays, " which may include short‐term or long‐term breaks from medication. The present study utilized fluorodeoxyglucose (FDG) positron emission tomography (PET) to analyze the effects of chronic oral MP use and abstinence on brain glucose metabolism (BGluM) in rats at two different doses: high dose (HD) and low dose (LD). The schedule of treatment was 3 weeks on‐treatment and 1 week off‐treatment for a period of 13 weeks, followed by an abstinence period of 4 total weeks. Results showed that chronic MP treatment using this schedule did not lead to significant changes in BGluM when comparing the control to HD MP groups. However, significant activation in BGluM was observed after periods of abstinence between control and HD MP rats in the following brain regions: the trigeminal nucleus, reticular nucleus, inferior olive, lemniscus, mesencephalic reticular formation, inferior colliculus, and several areas of the cerebellum. These brain regions and functional brain circuit play a role in facial sensory function, the auditory pathway, organizing connections between the thalamus and cortex, motor learning, auditory function, control over eye movement, auditory information integration, and both motor and cognitive functions. These results, when considered with previous studies, indicate that MP schedule of use may have differing effects on BGluM. BGluM following long‐term MP use was dependent on MP dose and schedule of use in rats. This study was conducted in non‐ADHD model rats with the aim to establish an understanding of the effects of MP itself, especially given the growing chronic off‐label and prescribed use of MP. Further studies are needed for analysis of the drug's effects on an ADHD model. Abstract : This experiment analyzed the effects of chronic oral methylphenidate (MP) administration and abstinence on 71, 4‐week‐old, all male, Sprague‐Dawley rats using FDG‐PET. Results indicate no significant differences between experimental and control groups after 13 weeks of chronic use; however, changes in brain glucose activation were observed following abstinence.